The long-term effects of loan guarantees on SME performance - Bertoni, Fabio; Colombo, Massimo G.; Quas, Anita (Journal of Corporate Finance, 2023)
We estimate the treatment effect of guaranteed loans on the growth of a large sample of French small and medium-sized enterprises (SMEs). The nature of our sample allows us to estimate the treatment effect up to 10 years after the treatment and to consider several performance measures and moderating factors. Our findings indicate that beneficiaries of guaranteed loans experience significantly higher growth in sales, employment, and total assets than otherwise similar companies. The effects are long lasting, do not entail a slowdown in productivity growth, are mostly driven by organic growth rather than by external acquisitions, and are larger in firms that are typically more financially constrained (young or small). Guaranteed-loan beneficiaries are also more likely to survive than non-beneficiaries. Our results are consistent across different identification strategies (matching, difference-in-differences, instrumental variable estimation) and control group choices.